Analysis on synergies and trade-offs in green building development: from the perspective of SDG 11. Issue 4 (2nd October 2019) - Zhu, Jing; Cao, Ying; Zhai, Jianyu; Zhao, Xi; Zhao, Yuqing; Kang, Shenghong
ABSTRACT: The 2030 Agenda for Sustainable Development is a prospect for the future development of all countries in the world. Its core is to set up the Sustainable Development Goals for the year of 2030, and develop a series of institutional mechanisms around SDGs to promote its implementation. The SDGs include 17 goals, of which SDG 11 is to make cities and human settlements inclusive, safe, resilient and sustainable. Green building can play a positive role in the implementation of SDG 11. However, the entire process of green building development involves multiple stakeholders and various professional fields, which play different roles where may be positive synergies or negative trade-offs in the whole process. This paper uses the nexus approaches to clarify how multiple stakeholders and professions interact with each other in the green building development with the aim of promoting SDG 11.